The Influence Of Socio-Economic Factors On The Interest Of Young Men And Women In Working In The Informal Sector In Denpasar City - Ida Bagus Putu Purbadharmaja (International Journal of Management Research and Economics, 2025)
The informal sector has a good development to advance the regional economy, especially in stimulating the economy of the community both at the lower and middle levels. In Denpasar City, the informal sub-sector is motivated by the increasing economic needs and the higher number of job seekers which is not proportional to the capacity in the labor market, so this can be an alternative to getting work, especially for members of the Sekaa Teruna Teruni as future productive age who is looking for work to be able to better take opportunities creatively and innovatively. To assist the Denpasar City Government in reducing unemployment and encouraging innovative economic growth, especially among youth, this study aims to examine the interest of Sekaa Teruna members in informal sector businesses in relation to socio-economic conditions.This study employs proportional random sampling with primary data, using a logit model for multiple regression analysis with 100 respondents as samples. The results of the study indicate that the income of families, the size of family units, and educational levels minimally influence the willingness of Sekaa Teruna Teruni members to engage in the informal sector of Denpasar City; however, the cost of continuing education and the necessity.